Studi Permukaan Produk Berbahan PLA Hasil Fabrikasi Menggunakan Mesin 3D Printer Jenis Fused Deposition Modelling (FDM) dengan Variasi Kecepatan Printing - Hariyanto, Satriawan Dini; Nurhayati, Nurhayati; Badrawada, I Gusti Gde (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
A study of the surface of the fabrication process using the fused deposition modeling (FDM) technique is needed to determine the suitability of the process parameters with the use of the product to be made. Products that have special characteristics that take advantage of the surface properties of fabricated using FDM are often encountered in technical applications involving fluids. This research is a preliminary study of the Water Contat Angle (WCA) study on polymer filaments made of PLA. In this study, the effect of printing speed on the width of polymer deposition and the gap distance between one deposit and another polymer deposit on the sample surface was observed and analyzed using image processing techniques. The printing speed is made to vary from 30 mm/s, 60 mm/s, and 90 mm/s. The relationship between printing speed and polymer deposition width produces a linear equation y = 0.0008 x + 0.28 and the gap width between filament deposition on the sample surface shows a linear equation relationship y = -0.0002 x + 0.0833